Increased Small Intestine Expression of Non‐Heme Iron Transporters in Morbidly Obese Patients With Newly Diagnosed Type 2 Diabetes. Issue 2 (29th December 2017) - Moreno‐Navarrete, José María; Rodríguez, Amaia; Becerril, Sara; Valentí, Víctor; Salvador, Javier; Frühbeck, Gema; Fernández‐Real, José Manuel
Abstract : Scope: To investigate intestinal markers of iron absorption in morbidly obese subjects according to glucose tolerance. Methods and results: Gene expression of both non‐heme ( SLC40A1 (ferroportin), SLC11A2 ) and heme iron ( SLC46A1 (HCP1), HMOX1 ) transporters is analyzed in 38 small intestine tissue samples [11 with normal glucose tolerance, 14 with glucose intolerance (GI), and 13 with newly diagnosed type 2 diabetes (T2D)]. SLC40A1 ( r = 0.43, p = 0.008) and SLC11A2 ( r = 0.35, p = 0.03) mRNA levels are positively correlated with ferritin‐to‐hepcidin ratio and with fasting glucose, being significantly increased in patients with T2D. Only ferroportin is negatively associated with serum hepcidin ( r = –0.617, p < 0.0001). In multivariate regression analysis, fasting glucose contributes independently to intestinal SLC40A1 ( p = 0.009) and SLC11A2 ( p = 0.04) variance after controlling for age, sex, and BMI. When circulating hepcidin is incorporated into the model, fasting glucose contributes significantly and independently to intestinal SLC40A1 ( p = 0.02), but not to SLC11A2 ( p = 0.07) variance. SLC46A1 and HMOX1 are similar in all groups. Conclusion: The expression of ferroportin and SLC11A2 is increased in the intestine of patients with T2D in association with iron stores and serum hepcidin levels. Increased intestinal iron absorption is a potential mechanism that could explain the increased body iron stores frequently observed in patients with T2D. Abstract : Decreased circulating hepcidin levels in patients with newly diagnosed type 2 diabetes is associated with increased non‐heme iron transporters ( SLC40A1 and SLC11A2 ) mRNA in the small intestine, suggesting that increased intestinal iron absorption is a potential mechanism that could explain the increased body iron stores frequently observed in patients with T2D.